Structural basis for the second step of group II intron splicing - Russell T. Chan (Nature Portfolio, 2018)
Group II introns are large, self-splicing RNAs that catalyze their own excision from pre-mRNA molecules. Here the authors determine the 3.7 Å crystal structure of the group II intron in the stage immediately before the second step of splicing and present a complete model for the second step of group II intron splicing.